The Chancellor manuscript - Ludlum, Robert, 1927-2001. (New York : Dial Press, 1977)
Did J. Edgar Hoover die a natural death? Or was he murdered? When a group of high-minded and high-placed intellectuals known as Inver Brass detect a monstrous threat to the country in Hoover$1 (Bs unethical use of his scandal-ridden private files, they decide to do away with him$1 (Bquietly, efficiently, with no hint of impropriety. Then bestselling thriller writer Peter Chancellor stumbles onto information that makes his previous books look like harmless fairy tales. Now Chancellor and Inver Brass are on a deadly collision course, spiraling across the globe in an ever-widening arc of violence and terror. All roads lead to a showdown that will rip the nation$1 (Bs capital apart$1 (Bleaving only one damning document to survive.s
Keywords: Adventure -- Action -- History